(3JMaI GdGTQGa deYQaI GdGWQGas - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s ((3GdMQe GdTQja s)
(3ChdgG (B:s
(3SYjO Hf GdeSjH MOjK cd MSfI jYedgG GHf GOe adg GdMOjK s
(3BNQgG (B:s
(3MOjK GfgG hUaJ dgG Sef HbQ ef hLY jMdbgG BNQ GdcJGH s
(3fSNI ebGHdI heYGQVI hebQhAIs
(3jHOC ef GKfGA MQa GdSjf hjfJgi HBNQ GdcJGHs
(3YdjgG NWhW hJbQjQGJ dHYV GdYdeGAs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs